Transcriptome Profiling Revealed Multiple rquA Genes in the Species of Spirostomum (Protozoa: Ciliophora: Heterotrichea) - Mukhtar, Irum; Wu, Siyi; Wei, Shurong; Chen, Ruanni; Cheng, Yunying; Liang, Chen; Chen, Jianming (Frontiers in Microbiology, 2021)
Adaptation to life at different oxygen tensions plays a role in protozoan ecology and controls the distribution of different species in anoxic habitats. The ciliate genus Spirostomum comprises ten morphospecies, inhabiting fresh or low salinity water globally where these species are considered as bioindicators. Exploration of the genes involved in anaerobic pathway is essential to provide a deeper understanding of microbial survival under oxygen-depleted environment. The rhodoquinol-dependent fumarate reduction for respiration under anoxic conditions has been reported in the many species from the class Heterotrichea. Although Spirostomum is relatively easily identified in different environments, and is a good model for applied ecology and symbiosis research, lacks deep molecular investigations on RquA for rhodoquinone (RQ) biosynthesis. In the present study, three Spirostomum species (S. ambiguum, S. subtilis and S. teres) collected from freshwater habitat in Fuzhou, China, were investigated for molecular evidence of RquA. We report here the transcriptome data obtained by RNA sequencing (RNAseq) of Spirostomum species. Analysis of the transcriptome indicates that Spirostomum species potentially use rhodoquinol dependent fumarate reduction to respire in the oxygen-depleted habitats and have at least two to three diverse RquA.